Blockchain in the Food Supply Chain: A Literature Review and Bibliometric Analysis - Wahyuni, Hana Catur; Alfan Rosyid, Mochamad; Sabrina, Bilqis; Gunawan, Ivan; Tieman, Marco (Universitas Ahmad Dahlan, 2025)
The food supply chain, a complex network of interconnected systems, faces numerous challenges, including food safety, traceability, and sustainability. Blockchain technology, with its inherent properties of immutability, transparency, and security, offers a promising solution to address these challenges. This systematic literature review aims to explore the current state of research and identify emerging trends in the application of blockchain technology to food supply chains. A comprehensive search of the Scopus database yielded 825 articles published between 2017 and 2023. The analysis focused on 161 articles that met specific inclusion criteria. Key themes identified in the literature include traceability, sustainability, food safety, halal food, and circular economy. Blockchain technology offers the potential to enhance transparency, efficiency, and sustainability in the food supply chain by enabling real-time tracking, reducing food waste, and ensuring food safety. The bibliometric analysis revealed a growing research community, with India emerging as a significant contributor. International collaboration is crucial for advancing the field and sharing knowledge. Future research directions include interdisciplinary collaboration, standardization, security, consumer education, and scalability. This study contributes to advancing these research directions by providing insights that enable researchers and industry practitioners to harness the full potential of blockchain technology in fostering a more efficient, transparent, and sustainable food supply chain.